Climate of Almaty city for the last 130 years (Eurasian Journal of Ecology, 2016)
The climate is one of the major physiographic features of any city. In this respect, it is interesting to change the basic values of climate south of the capital and the largest city of the Republic of Kazakhstan - Almatyfor the period of the city’s weather station, ie for 130 years, from 1880 to 2010 Features of the climate regime are due primarily to its geographical position.
Keywords: the period; cyclical fluctuations; harmonics; harmonic analysis polynomial; continental climate; the amplitude of temperature change.